2009
DOI: 10.1158/1535-7163.mct-09-0462
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer mechanisms of doxorubicin and zoledronic acid in breast cancer tumor growth in bone

Abstract: Patients with advanced breast cancer frequently develop bone metastases, and at this stage, the disease is considered incurable. Here, we show that a 6-week course of weekly administration of doxorubicin (2 mg/kg), followed 24 hours later by the bisphosphonate zoledronic acid (100 μg/kg), causes substantial inhibition of MDA-MB-436 breast tumor burden in bone of immunocompromised mice, compared with administration of the single agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
54
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(61 citation statements)
references
References 47 publications
6
54
0
1
Order By: Relevance
“…PyMT tumour development, thus, closely mimics the development and progression of human disease. In accordance with previous studies [28][29][30]40], we found that administration of clinically relevant doses doxorubicin (2 mg/kg) followed 24 h later by zoledronic acid (100lg/kg) elicited dramatic anti-tumour effects. Mammary tumours from all 12-to 13-week-old PyMT-MMTV animals that had received combination therapy for 6 weeks were histologically similar, and also comparable in size, to tumours dissected from 6-week-old untreated mice, implying that this therapeutic schedule inhibits essential steps in mammary tumour development and progression.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…PyMT tumour development, thus, closely mimics the development and progression of human disease. In accordance with previous studies [28][29][30]40], we found that administration of clinically relevant doses doxorubicin (2 mg/kg) followed 24 h later by zoledronic acid (100lg/kg) elicited dramatic anti-tumour effects. Mammary tumours from all 12-to 13-week-old PyMT-MMTV animals that had received combination therapy for 6 weeks were histologically similar, and also comparable in size, to tumours dissected from 6-week-old untreated mice, implying that this therapeutic schedule inhibits essential steps in mammary tumour development and progression.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have used human breast cancer cells engrafted either subcutaneously or directly into the tibiae of immunocompromised mice, demonstrating clear effects of combination treatment on rapidly proliferating, immortalised cell lines in vivo [28][29][30]40]. To investigate treatment efficacy on spontaneous mammary tumour development in situ we have now studied immunocompetent FVB mice expressing mouse polyomavirus T antigen [31][32][33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are also a wealth of preclinical data reporting that ZOL-induced FPP synthase inhibition has both direct and indirect antitumor effects in breast cancer (3). Preclinical studies have shown sequence-dependent synergy between chemotherapy agents and ZOL (4,5) with maximum effects observed when ZOL is administered 24 hours after chemotherapy. Six cycles of weekly treatment with clinically relevant doses of doxorubicin followed 24 hours later by ZOL inhibited subcutaneous tumor growth in an in vivo mouse model of breast cancer soft tissue disease in the absence of tumor-associated bone disease (6).…”
Section: Introductionmentioning
confidence: 99%
“…14) Zoledronic acid (ZOL) is one of the most potent drugs owing to its direct and indirect antitumor effects, 15) and it has been effectively used for the treatment of several cancer cell types such as breast and prostate cancers, acute promyelocytic leukemia, including pancreatic cancers. [16][17][18][19][20] Moreover, ZOL was reported to have an augmenting effect when used with other anticancer agents, 21,22) molecular target agents, 23,24) and radiotherapy. 25) Statins have an inhibitory action on 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA), a rate-limiting enzyme in the mevalonate pathway.…”
mentioning
confidence: 99%